Let's assume that Tony had x amount of money at first.
According to the given information, he spent 650.00 from that total amount and has 3/13 of the remaining amount left.
So, the remaining amount he has left is (1 - 3/13)x = 10/13 x.
We know that the remaining amount is equal to 10/13 of his initial amount. So, we can set up the equation:
10/13x = remaining amount = x - 650
Now we can solve for x:
10/13x + 650 = x
Multiplying both sides of the equation by 13:
10x + 8450 = 13x
Subtracting 10x from both sides:
8450 = 3x
Dividing both sides by 3:
x = 2816.67
Therefore, Tony had 2816.67 at first.
After spending 650.00of his money tony had 3/13 left. How much had he at first
3 answers
to make a long story short:
3/13 x = 650
x = 13(650)/3 = $ 2816.67
3/13 x = 650
x = 13(650)/3 = $ 2816.67
To make a short story correct, he spent 10/13 = 650
13/10 * 650 = 845 to start with
13/10 * 650 = 845 to start with